Protein Coding Low‐Copy rpb2 and ef1‐α Regions Are Viable Fungal Metabarcoding DNA Markers Which Can Supplement ITS for Better Accuracy - Vasilii Shapkin; Miroslav Caboň; Miroslav Kolařík; Katarína Adamčíková; Petr Baldrian; Tereza Michalová; Tomáš Větrovský; Slavomír Adamčík (Ecology and Evolution, 2025)
ABSTRACT The nuclear ribosomal DNA Internal Transcribed Spacer (ITS) region is used as a universal fungal barcode marker, but often lacks a significant DNA barcoding gap between sister taxa. Here we tested the reliability of protein coding low‐copy genes as alternative barcode markers. Mock communities of three unrelated agaric genera (Dermoloma, Hodophilus, and Russula) representing lineages of closely related species were sequenced by the Illumina platform targeting the ITS1, ITS2, the second largest subunit of RNA polymerase II gene (rpb2) and the transcription elongation factor 1‐alpha gene (ef1‐α) regions. Species representation and their relative abundances were similar across all tested barcode regions, despite a lower copy number in protein coding markers. ITS1 and ITS2 required more sophisticated sequence filtering because they produced a high number of chimeric sequences requiring reference‐based chimera removal and had a higher number of sequence variants per species. Although clustering of filtered ITS sequences resulted in an average higher number of correctly clustered units at optimal similarity thresholds, these thresholds varied substantially among genera. Best‐fitted thresholds of low‐copy markers were more consistent across genera but frequently lacked species resolution due to low intraspecific variability. At some thresholds, we observed multiple species lumped together, and at the same time, species split into multiple partial clusters, which should be taken into consideration when assessing the best clustering thresholds and taxonomic identity of clusters. To achieve the best taxonomic resolution and improve species detection, we recommend combining different markers and applying additional reference‐based sorting of clusters. The current availability of rpb2 and ef1‐α reference sequences in public databases is far from being complete for all fungal groups, but a combined marker approach can be used for group‐specific studies that can build reference data for their own purposes.